Effect of Water Stress and Antitranspirants on Chlorophyll Contents of Dalbergia sissoo Roxb. Leaves - Sagta, H. C.; Nautiyal, S. (Indian Forester, 2002)
Four months old seedlings of Dalbergia sissoo Roxb. were subjected to water stress treatment by withholding watering for 7, 14, 28 days and compared with the control (daily watering). In addition, seedlings were treated with two concentrations of three antitranspirants viz., Cycocel (CCC), Maleic Hydrazide (MH) and Sodium Benzoate (SB) with the objective of maintaining water economy in seedling through reduced loss of water by limiting the transpiration. The study was carried out for 6 months to determine the stress tolerance and changes in chlorophyll content of this species. Variations with in the treatment of water stress, antitranspirants concentrations and months were found highly significant (P < O.Ol). The increasing level of water stress and antitranspirants concentration decreases the chlorophyll contents (a, b and total). The maximum chlorophyll contents in leaves were observed in plants untreated by antitranspirants at daily watering. However, the minimum chlorophyll contents were observed at 28 days watering interval under all the treatments. Higher concentration of antitranspirants decreases chlorophyll contents more adversely as compare to lower concentration. Sodium benzoate was found to be more effective to decrease the chlorophyll content as compared to other antitranspirants at lower concentration. The effect of water stress in combination with antitranspirants found to reduce the chlorophyll-b content to larger extent as compared to chlorophyll-a.